The strange death of Europe : immigration, identity, Islam - Murray, Douglas, 1979- (London : Bloomsbury Continuum, an imprint of Bloomsbury Publishing Plc, 2017)
This book is not only an analysis of demographic and political realities in Europe, but also an eyewitness account of a continent in self-destruct mode. It includes reporting from across the entire continent, from the places where migrants land to the places they end up, from the people who appear to welcome them in to the places which cannot accept them.
The beginning -- How we got hooked on immigration -- The excuses we told ourselves -- 'Welcome to Europe' -- Multiculturalism -- They are here -- Prophets without honour -- Early warning sirens -- The tyranny of guilt -- The pretense of repatriation -- Learning to live with it -- Tiredness -- We're stuck with this -- Controlling the backlash -- The feeling that the story has run out -- The end -- What might have been -- What will be.
Includes bibliographical references and index.
105149
Keywords: Economic history; Politics and government; Social conditions; Europe -- Social conditions -- 21st century; Europe -- Politics and government -- 21st century; Europe -- Economic conditions -- 21st century; Europe